Patterns of Lifetime Criminality in Mentally Disordered Offenders – Findings From a Nationally Representative Cohort - Krona, Hedvig; Anckarsäter, Henrik; Nilsson, Thomas; Hofvander, Björn (Frontiers in Psychiatry, 2021)
Background Treatment of mentally disordered offenders (MDOs) is challenging as their behaviour and clinical conditions can be traced to a complex constellation of major mental disorders, substance use and antisocial lifestyle. Finding subgroups of these offenders, which could guide treatment and risk assessment, is desirable. There are few long-term, prospective studies of risk factors for persistent criminal behaviour among MDOs. Aims The aims are (1) to provide a map of lifetime criminality in MDOs, (2) to identify subgroups of offenders, and (3), if such clusters exist, to test whether they differ in lifetime criminality and patterns of negative events during in-patient treatment. Methods Background data on all offenders from the Malmö University Hospital catchment area sentenced to forensic psychiatric in-patient treatment 1999-2005 (n = 125) was collected. Data on negative events during treatment (violence, threats, absconding and substance use) from date of admittance until discharge or until June 30, 2008 was gathered. Court decisions for 118 of the cohort-individuals were collected from the 1st of January 1973 until December 31, 2013. We used hierarchical cluster analysis to identify subgroups and MANOVA-analysis to examine differences between these clusters on lifetime criminality variables and negative events. A MANCOVA was used to control for time in treatment. Results The cohort was sentenced to a total of 3380 crimes (944 violent) during the study period. Median age at first crime was 20 years (range 15-72), and at first violent crime 27 years (range 15-72). A subgroup (n = 26) was characterized by childhood adversities, neurodevelopmental disorders and later substance use and was more often associated with substance-related crimes, financial crimes and lower age at first crime. During treatment, this cluster showed higher rates of substance use and threats. When controlling for treatment time, no differences in negative events were found. Conclusions This study replicated findings from prison populations of the existence of a more criminally persistent phenotype characterised by early-onset neurodevelopmental and behaviour disorders, childhood adversities and later substance use disorders. We did not find this cluster of variables to be related to negative events during inpatient treatment when controlling for length of stay.